Analisis Faktor - Faktor Yang Mempengaruhi Kinerja Pegawai (Studi Empirik Pada Upt Pendidikan Dasar Dan Luar Sekolah Kecamatan Mojosongo Kabupaten Boyolali) - LAILA, FALAH; , Wiyadi, Ph.D; , Soepatini, Ph.D (2016)
This research aims to analyze the effect of Leadership Style, Work Discipline, Compensation, Job Satisfaction, on Performance. The data used in this research is the primary data. They were obtained from the responses of 91 respondents on the questionaires given to the officials of UPT Pendidikan Dasar dan Luar Sekolah Kecamatan Mojosongo Kabupaten Boyolali by quota sampling methods. The data analysis device used in this research is multilinear regression. Based on the test of instrument all variables are valid and reliable. The results of the classical assumption examination indicate that the data normally distribute, moreover there are no multicolinearity and heteroschedastisity. From the findings of the data analysis, it is found that leadership style, work discipline, compensation, and Job satisfaction, affect significantly on the performance of the officials.